Pengembangan Panduan Transformasi Administrasi Pembelajaran berbasis Digital melalui Google Aplikasi - Widia Sukma Sari; Bambang Ismanto; Tri Nugroho Budi Santoso (IKIP PGRI Bojonegoro, 2022)
life, including education. Indirectly, it requires the digitalization ability of teachers. However, it still faces various problems with many factors. The purpose of this research is to produce a product development guide to become a solution of the problems encountered. It is development research (R&D) with the ADDIE development design model. The subjects of this research are teachers at the Christian Business and Management Vocational School in Salatiga. The data collection techniques applied are observations, interviews, documentations, and expert judgment. The results obtained from this guide through expert validation are as follows: material expert assessment 3.6 with the